Hadith #2128 - Sunan Abi Dawud - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ibn Jurayj ابن جريج; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Muhammad bin Ma'mar bin Rabi' محمد بن معمر بن ربعي القيسي البحراني; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) commanded me to send a woman to her husband before he gave something to her. Abu Dawud said: The narrator Khaithamah did not hear (any tradition) from ‘Aishah.
Grade: Da'if

Hadith #2130 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Hassan ibn Ali bin Abi Talib; Ibn Jurayj ابن جريج; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Abi Dawud)
When the Prophet (ﷺ) congratulated a man on his marriage, he said: May Allah bless for you, and may He bless on you, and combine both of you in good (works).
Grade: Sahih

Hadith #2184 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Yunus bin Jubair said “I asked ‘Abd Allah bin ‘Umar “A man divorced his wife while she was menstruating? He said do you know ‘Abd Allah bin ‘Umar? He said, yes. ‘Abd Allah bin ‘Umar divorced his wife while she was menstruating. So, ‘Umar came to the Prophet (ﷺ) and asked him (about this matter). He said Command him to take her back in marriage he may the divorce her in the beginning of the waiting period. I (Ibn Jubair) asked him “Will this divorce be counted? He said “Wh
Grade: Sahih

Hadith #2188 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
Ibn Abbas said: There remained one more pronouncement of divorce for you. The Messenger of Allah (ﷺ) took the same decision. Abu Dawud said: I heard Ahmad b. Hanbal say: ‘Abd al-Razzaq said that Ibn al-Mubarak said to Ma’mar: Who is this Abu al-Hasan ? He bore a big rock. Abu Dawud said: Al-Zuhri has narrated (traditions) on the authority of this Abu al-Hasan. Al-Zuhri said: He was lawyer, and al-Zuhri narrated many traditions from Abu al-Hasan. Abu Dawud said: Abu al-Hasan is well known n
Grade: Da'if

Hadith #2195 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
Divorced women shall wait concerning themselves for three monthly periods. Nor is it lawful for them to hide what Allah hath created in their wombs. This means that if a man divorced his wife he had the right to take her back in marriage though he had divorced her by three pronouncements. This was then repealed (by a Qur’anic verse). Divorce is only permissible twice.
Grade: Hasan Sahih

Hadith #2199 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Tawus said A man called Abu Al Sahba used to ask Ibn ‘Abbas questions frequently. He asked “Do you know that when a man divorced his wife by three pronouncement before sexual intercourse with her, they (the people) made it a single divorce during the time of the Apostle of Allaah(ﷺ), of Abu Bakr and in the early phase of the caliphate of ‘Umar?” Ibn “Abbas said “Yes, when a man divorced his wife by three pronouncement before sexual intercourse they made it a single divorce during t
Grade: Da'if

Hadith #2276 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hilal bin Abi Maymuna هلال بن علي بن أسامة; Ibn Jurayj ابن جريج; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
A woman said: Messenger of Allah, my womb is a vessel to this son of mine, my breasts, a water-skin for him, and my lap a guard for him, yet his father has divorced me, and wants to take him away from me. The Messenger of Allah (ﷺ) said: You have more right to him as long as you do not marry.
Grade: Hasan

Hadith #2296 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Maimun bin Mihram said “I came to Median and went to Sa’id bin Al Musayyab”. I said (to him) Fathimah daughter of Qais was divorced and she shifted from her house. Sa’id said “This woman has perverted people. She was arrogant so she was placed with Ibn Umm Makhtum, the blind.”
Grade: Da'if

Hadith #2310 - Sunan Abi Dawud - Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
‘Abd Allaah (bin Masud) said “I asked Apostle of Allaah(ﷺ) which sin is the gravest?” He replied “That you associate someone with Allaah, while He has created you”. I again asked “Which then?” He replied “That you commit adultery with the wife of your neighbor.” Allaah then revealed the following Qur’anic verse in support of the statement of the Prophet (ﷺ) “Those who invoke not with Allaah any other god nor slay such life as Allaah has made sacred except for just cause
Grade: Sahih

Hadith #2369 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Makhul al-Shami/al-Damashiqi مكحول الشامي; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came to a man at al-Baqi’ while he was cupping on the 18th of Ramadan ; he (the Prophet) was holding my hand. Thereupon he said: A man who cups and a man who gets himself cupped break their fast. Abu Dawud said: The narrator Khalid al-Hadhdha’ transmitted a similar tradition from Abu Qilabah through a different chain of narrators mentioned by the narrator Ayyub.
Grade: Sahih

Hadith #2598 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) proceeded on journey, he would say: O Allah, Thou art the Companion in the journey, and the One Who looks after the family; O Allah, I seek refuge in Thee from the difficulty of travelling, finding harm when I return, and unhappiness in what I see coming to my family and property. O Allah, make the length of his journey short for us, and the journey easy for us.
Grade: Sahih

Hadith #2780 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin Ka'b عبد الرحمن بن عبد الله بن كعب بن مالك; Abdur-Razzaq عبد الرزاق بن همام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hassan ibn Ali bin Abi Talib; Ibn Jurayj ابن جريج; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
Anas bin Malik said “A youth of Aslam said “Apostle of Allaah(ﷺ), I wish to go on an expedition, but I have no property to make myself equipped. He said “go to so and so Ansari who prepared equipment(for the battle), but he fell ill and tell him that the Apostle of Allaah(ﷺ) has conveyed his regards to you, and then tell him “Give him all the equipment you have made. He came to him and told him that. He said to his wife “O so and so, give him all the equipment I have made and do no
Grade: Sahih

Hadith #2845 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Were dogs not a species of creature I should command that they all be killed; but kill every pure black one.
Grade: Sahih

Hadith #3004 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibn Jurayj ابن جريج; ibn Umar; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Musa bin 'Uqba موسى بن عقبة; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
AbdurRahman ibn Ka’b ibn Malik reported on the authority of a man from among the companions of the Prophet (ﷺ): The infidels of the Quraysh wrote (a letter) to Ibn Ubayy and to those who worshipped idols from al-Aws and al-Khazraj, while the Messenger of Allah (ﷺ) was at that time at Medina before the battle of Badr. (They wrote): You gave protection to our companion. We swear by Allah, you should fight him or expel him, or we shall come to you in full force, until we kill your fighters an
Grade: Sahih

Hadith #3029 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Umar ibn al-Khattab (Sunan Abi Dawud)
Ibn ‘Abbas said that the Prophet (ﷺ) gave three instructions saying “Expel the polytheists from Arabia, reward deputations as I did”. Ibn ‘Abbas said “He either did not mention the third or I have been caused to forget it. Al Humaidi said on the authority of Sufyan that Sulaiman said “I do not know whether Sa’id mentioned the third and I forgot or he himself did not mention it.”
Grade: Sahih

Hadith #3139 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
He combined two persons from among the martyrs of Uhud in one garment.
Grade: Sahih

Hadith #3147 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Muhammad b. Sirin used to learn how to wash the dead from Umm ‘Atiyyah: he would was with lotus leaves twice and with water and camphor for the third time.
Grade: Sahih

Hadith #3192 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ibn Jurayj ابن جريج; Yahya bin Sbyh يحيى بن صبيح; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
There were three times at which the Messenger of Allah (ﷺ) used to forbid us to pray or bury our dead – when the sun begins to rise till it is fully up, when the sun is at its height midway till it passes the meridian, and when the sun draws near to setting till it sets, or as he said.
Grade: Sahih

Hadith #3224 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) prayed over the martyrs of Uhud after eight years like a man who bids farewell to the living and dead.
Grade: Sahih

Hadith #3225 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Hafs bin Ghyath حفص بن غياث; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق; Uthman bin Muhammad (Sunan Abi Dawud)
I heard the Prophet (ﷺ) forbid to sit on the grave, to plaster it with gypsum, and to build any structure over it.
Grade: Sahih

Hadith #3293 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibn Jurayj ابن جريج; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري (Sunan Abi Dawud)
Uqbah consulted the Prophet (ﷺ) about his sister who took a vow to perform hajj barefooted and bareheaded. So he said: Command her to cover her head and to ride, and to fast three days.
Grade: Da'if

Hadith #3298 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibn Jurayj ابن جريج; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The tradition about the sister of ‘Uqbah b. ‘Amir as narrated by Hisham, but he made no mention of the sacrificial animal. In his version he said: Ask your sister to ride. Abu Dawud said: Khalid narrated it from ‘Ikrimah to the same effect as narrated by Hisham.
Grade: Sahih

Hadith #3301 - Sunan Abi Dawud - Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw a man that he was supported between his sons. He asked about him, and (the people) said: He has taken a vow to walk (on foot). Thereupon he said: Allah has no need that this man should punish himself, and he ordered him to ride. Abu Dawud said: ‘Amr b. Abi ‘Amir has also narrated a similar tradition from al-A’raj on the authority of Abu Hurairah from the Prophet (ﷺ).
Grade: Sahih

Hadith #3305 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Hafs bin 'Umar bin 'Abdur Rahman B. 'Auf حفص بن عمر بن عبد الرحمن بن عوف; Ibn Jurayj ابن جريج; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Umar bin 'Abdur Rahman bin Awf عمر بن عبد الرحمن بن عوف; Umar ibn al-Khattab (Sunan Abi Dawud)
A man stood on the day of Conquest (of Mecca) and said: Messenger of Allah, I have vowed to Allah that if He grants conquest of Mecca at your hands, I shall pray two rak’ahs in Jerusalem. He replied: Pray here. He repeated (his statement) to him and he said: Pray here. He again repeated (his statement) to him. He (the Prophet) replied: Pursue your own course, then. Abu Dawud said: A similar tradition has been narrated by ‘Abd al-Rahman b. ‘Awf from the Prophet (ﷺ).
Grade: Sahih

Hadith #3372 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I asked Abu Zinad about the sale of fruits before they were clearly in good condition, and what was said about it. He replied: Urwah ibn az-Zubayr reports a tradition from Sahl ibn Abi Hathmah on the authority of Zayd ibn Thabit who said: The people used to sell fruits before they were clearly in good condition. When the people cut off the fruits, and were demanded to pay the price, the buyer said: The fruits have been smitten by duman, qusham and murad fruit diseases on which they used to dispu
Grade: Sahih

Hadith #3412 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
When the Prophet (ﷺ) conquered Khaibar. He then narrated it like the tradition of Zaid (b. Abu al-Zarqa’). This version has: He then assessed the produce of the palm-trees and said: I take the job of picking the fruit myself, and I shall give you half of (the amount) I said.
Grade: Hasan

Hadith #3414 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
When Allah bestowed Khaybar on His Prophet (ﷺ) as fay’ (as a result of conquest without fighting), the Messenger of Allah (ﷺ) allowed (them) to remain there as they were before, and apportioned it between him and them. He then sent Abdullah ibn Rawahah who assessed (the amount of dates) upon them.
Grade: Sahih

Hadith #3444 - Sunan Abi Dawud - Abdullah bin Mkhld عبد الله بن مخلد; Abu Hurairah; Ibn Jurayj ابن جريج; Makki bin Ibrahim bin Bashayr مكي بن إبراهيم بن بشير; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If anyone buys sheep whose udders have been tied up, he has option for three days: he may return it if he desires with a sa’ of any grain, not (necessarily) wheat.
Grade: Sahih

Hadith #3469 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Ma'mar bin Rabi' محمد بن معمر بن ربعي القيسي البحراني; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
In the time of the Messenger of Allah (ﷺ) a man suffered loss affecting fruits he had bought and owed a large debt, so the Messenger of Allah (ﷺ) said: Give him sadaqah (alms). So the people gave him sadaqah (alms), but as that was not enough to pay the debt in full, the Messenger of Allah (ﷺ) said: Take what you find. But that is all you may have.
Grade: Sahih

Hadith #3470 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If you were to sell dried dates to your brother and they were smitten by blight, it will not be allowable for you to take your brother’s property unjustly.
Grade: Sahih

Hadith #3512 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Ibn Mas’ud sold slaves to al-Ash’ath b. Qais. He then narrated the rest of the tradition to the same effect with some variation of words.
Grade: Sahih

Hadith #3514 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Hurairah; al-Hasan bin al-Rabi' al-Bajli الحسن بن الربيع; Ibn Jurayj ابن جريج; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) decreed the right to buy the neighboring property applicable to everything which is not divided, but when boundaries are fixed and separate roads made, there is no option.
Grade: Sahih

Hadith #3555 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The life-tenancy which the Messenger of Allah (ﷺ) allowed was only that one should say: It is for you and your descendants. When he says: It is yours as long as you live, it returns to its owner.
Grade: Sahih

Hadith #3713 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Ibn Jurayj ابن جريج; Ubaid bin 'Umayr bin Qatada عبيد بن عمير بن قتادة (Sunan Abi Dawud)
Raisins were steeped for the Prophet (ﷺ) and he would drink it in the morning and the night after, the following day and the night after. He then gave orders and it was given to servants to drinks or poured away. Abu Dawud said: That “it was given to servants to drink” means before it spoiled. Abu Dawud said: Abu ‘Umar Yahya al-Bahrani.
Grade: Sahih

Hadith #3730 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I was in the house of Maymunah. The Messenger of Allah (ﷺ) accompanied by Khalid ibn al-Walid entered. Two roasted long-tailed lizards (dabb) placed on the sticks were brought to him. The Messenger of Allah (ﷺ) spat. Khalid said: I think that you abominate it, Messenger of Allah. He said: Yes. Then the Messenger of Allah (ﷺ) was brought milk, and he drank (it). The Messenger of Allah (ﷺ) then said: When one of you eats food, he should say: O Allah, bless us in it, and give us food (or no
Grade: Hasan

Hadith #3764 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
The Companions of the Prophet (ﷺ) said: Messenger of Allah (ﷺ) we eat but we are not satisfied. He said: Perhaps you eat separately. They replied: Yes. He said: If you gather together at your food and mention Allah’s name, you will be blessed in it. Abu Dawud said: If you are invited to a wedding feast before you, do not take it until the owner of the house (i.e. the host) allows you (to eat).
Grade: Hasan

Hadith #3807 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah (Sunan Abi Dawud)
that the Prophet (ﷺ) forbade payment for a cat. Ibn AbdulMalik said: to eat a cat and to enjoy its price.
Grade: Sahih

Hadith #3846 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Abbas; Ibn Jurayj ابن جريج; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
If the servant of any of you prepares food for him, and he brings it to him, while he had suffered its heat and smoke. He should make him sit with him to eat. If the food is scanty, he should put one or two morsels in his hand.
Grade: Sahih

Hadith #3917 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) heard a word, and he liked it, he said: We took your omen from your mouth.
Grade: Sahih

Hadith #4000 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ibn Jurayj ابن جريج; Sa'id bin Yahya bin Sa'id bin Aban سعيد بن يحيى بن سعيد بن أبان; Umm Salamah; Yahya bin Sa'id bin Aban bin Sa'id يحيى بن سعيد بن أبان بن سعيد (Sunan Abi Dawud)
The Prophet (ﷺ), AbuBakr, Umar and Uthman used to read “maliki yawmid-din (master of the Day of Judgment)”. The first to read maliki yawmid-din was Marwan. Abu Dawud said: This is sounder that the tradition which transmitted by al-Zuhri from Anas, and al-Zuhri from Salim, from his father (Ibn ‘Umar).
Grade: Da'if

Hadith #4002 - Sunan Abi Dawud - Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Umar bin Ata'a bin Wraz عمر بن عطاء بن وراز (Sunan Abi Dawud)
I was sitting behind the Messenger of Allah (ﷺ) who was riding a donkey while the sun was setting. He asked: Do you know where this sets ? I replied: Allah and his Apostle know best. He said: It sets in a spring of warm water (Hamiyah).
Grade: Sahih

Hadith #4014 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sat with us and my thigh was uncovered. He said: Do you not know that thigh is a private part ?
Grade: Sahih

Hadith #4098 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ibn Jurayj ابن جريج; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) cursed the man who dressed like a woman and the woman who dressed like a man.
Grade: Sahih

Hadith #4176 - Sunan Abi Dawud - Ammar ibn Yasir; Ibn Jurayj ابن جريج; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Nasr bin 'Ali bin Nasr bin 'Ali; Umar bin 'Ata'a bin Abi al-Khawar عمر بن عطاء بن أبي الخوار; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I came to my family at night (after a journey) with my hands chapped and they perfumed me with saffron. In the morning I went to the Prophet (ﷺ) and gave him a greeting, but he did not respond to me nor did he welcome me. He said: Go away and wash this off yourself. I then went away and washed it off me. I came to him but there remained a spot of it on me. I give him a greeting, but he did not respond to me nor did he welcome me. He said: Go away and wash it off yourself. I then went away and
Grade: Hasan

Hadith #4203 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: Jews and Christians do not dye (their beards), so act differently from them.
Grade: Sahih

Hadith #4229 - Sunan Abi Dawud - Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Umar bin Hafs bin Ghyath عمر بن حفص بن غياث (Sunan Abi Dawud)
I saw as-Salt ibn Abdullah ibn Nawfal ibn AbdulMuttalib wearing the signet-ring on his right small finger. I asked: What is this? He replied: I saw Ibn Abbas wearing his ring in this manner. He put its stone towards the upper part of his palm. Ibn Abbas also mentioned that the Messenger of Allah (ﷺ) used to wear his signet-ring in his manner.
Grade: Hasan Sahih

Hadith #4230 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ibn Jurayj ابن جريج; Muhammad bin 'Abdul Rahim bin Abi Zuhayr محمد بن عبد الرحيم بن أبي زهير البزاز; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء (Sunan Abi Dawud)
There is a devil along with each bell.
Grade: Da'if

Hadith #4273 - Sunan Abi Dawud - Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Sa'id bin Jubayr سعيد بن جبير الأسدي; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
I asked Ibn ‘Abbas (about the verse relating to intentional homicide in Surat An-Nisa’) He said: When the verse “Those who invoke not with Allah any other god, nor slay such life as Allah had made sacred, except for just cause” was revealed, the polytheists of Mecca said: We have killed the soul prohibited by Allah, invoked another god along with Allah for worship, and committed shameful deeds. So Allah revealed the verse “unless he repents, believes, and works righteous deeds, for All
Grade: Sahih

Hadith #4374 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ibn Jurayj ابن جريج; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
A Makhzumi woman used to borrow goods and deny having received them, so the prophet (ﷺ) gave orders that her hand should be cut off. The narrator than transmitted the rest of the tradition like that of al-laith, saying : So the prophet (ﷺ) had her hand cut off. Abu dawud said: Ibn Wahb transmitted this tradition from Yunus on the authority of al-Zuhri, and in this version he said al-Laith has said: A woman committed theft during the lifetime of the Prophet (ﷺ) on the occasion of the Conque
Grade: Sahih

Hadith #4384 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو (Sunan Abi Dawud)
A thief’s hand should be cut off for a quarter of a dinar and upwards. Ahmed b. Salih said: The amputation (of a thief’s hand) is for a quarter of a dinar and upwards.
Grade: Sahih

Hadith #4389 - Sunan Abi Dawud - Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
Marwan gave him some lashes and let him go.
Grade: Sahih

Hadith #4391 - Sunan Abi Dawud - Ibn Jurayj ابن جريج; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
The Prophet (ﷺ) said: Cutting of hand is not to be inflicted on one who plunders, but he who plunders conspicuously does not belong to us.
Grade: Sahih

Hadith #4426 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Ma’iz ibn Malik came to the Prophet (ﷺ) and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. He (the Prophet) said: You have testified to yourself four times. Take him away and stone him to death.
Grade: Sahih

Hadith #4427 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) said to Ma’iz ibn Malik: Perhaps you kissed, or squeezed, or looked. He said: No. He then said: Did you have intercourse with her? He said: Yes. On the (reply) he (the Prophet) gave order that he should be stoned to death. The narrator did not mention “on the authority of Ibn ‘Abbas”. This is Wahb’s version.
Grade: Sahih

Hadith #4436 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
A part of tradition has also been transmitted by al-Lajlaj from the Prophet (ﷺ) through a different chain of narrators.
Grade: Hasan

Hadith #4437 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and confessed before him that he had committed fornication with a woman whom he named. The Messenger of Allah (ﷺ) sent for the woman and asked her about it. But she denied that she had committed fornication. So he inflicted the prescribed punishment of flogging on him, and let her go.
Grade: Sahih

Hadith #4453 - Sunan Abi Dawud - Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
He called the witnesses who testified.
Grade: Sahih

Hadith #4461 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibn Jurayj ابن جريج; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
A similar tradition (to the No. 4445) has also been transmitted by Salamah ibn al-Muhabbaq from the Prophet (ﷺ). This version has: If she asked her to have intercourse with her voluntarily, then she and a similar slave-girl would be given to her mistress from his property.
Grade: Hasan

Hadith #4474 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Hassan ibn Ali bin Abi Talib; ibn Abbas; Ibn Jurayj ابن جريج; Ikrama عكرمة; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
When my vindication came down, the Prophet (ﷺ) mounted the pulpit and mentioned that, and recited the Qur’an. Then when he came down from the pulpit he ordered regarding the two men and the woman, and they were given the prescribed punishment.
Grade: Hasan

Hadith #4570 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس; Umar ibn al-Khattab (Sunan Abi Dawud)
‘Umar consulted the people about the compensation of abortion of woman. Al-Mughirah b. Shu’bah said: I was present with the Messenger of Allah (ﷺ) when he gave judgement that a male or female slave should testify you. So he brought Muhammad b. Maslamah to him. Harun added: He then testified him. Imlas means a man striking the belly of his wife. Abu Dawud said: I have been informed that Abu ‘Ubaid said: It (abortion) is called imlas because the woman causes it to slip before the time of d
Grade: Sahih

Hadith #4582 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Safwan bin Y'ala bin Umayya صفوان بن يعلى بن أمية; Ya'la bin Umayya; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a mukatab (a slave who has made an agreement to purchase his freedom) gifts blood-money or an inheritance, he can inherit in accordance with the extent to which he has been emancipated. Abu Dawud said: Wuhaib transmitted it from Ayyub, from ‘Ikrimah, on the authority of ‘Ali, from the Prophet (ﷺ): and Hammad b. Zaid and Isma’il have transmitted it in a mursal form (i.e the link of the Companion being missing) from Ayyub, from ‘Ikrimah, from the Prophet (ﷺ
Grade: Sahih

Hadith #4584 - Sunan Abi Dawud - al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ibn Jurayj ابن جريج; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
On this father’s authority, said: A servant of mine fought with a man and bit his hand and he drew away his hand. (One of) his front teeth fell out. So he came to the Prophet (ﷺ) who imposed no retaliation for his tooth, saying: Do you intend that he leaves his hand in your mouth so that you crunch it like a male camel ? He said: Ibn Abi Mulaikah told me on the authority of his grandfather that Abu Bakr (ra) imposed no retaliation on him for it, saying: May his tooth go away!
Grade: Sahih

Hadith #4606 - Sunan Abi Dawud - al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; Ibn Jurayj ابن جريج; ibn Mas'ud; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Atyq سليمان بن عتيق; Tlq bin Habib al-Nzy al-Bsry طلق بن حبيب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
If any one introduces into this affair of ours anything which does not belong to it, it is rejected. Ibn `Isa said: The Prophet (ﷺ) said: If anyone practices any action in a way other than our practice, it is rejected.
Grade: Sahih

Hadith #4846 - Sunan Abi Dawud - Ali bin Bhr bin Bry علي بن بحر بن بري; Amr bin al-Shryd عمرو بن الشريد; Ibn Jurayj ابن جريج; Ibrahim bin Maysara al-Ta'ifi إبراهيم بن ميسرة الطائفي; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) sat, he had his knees drawn up supported by his hands. Abu Dawud said: ‘Abd Allah b. Ibrahim was an old man and his traditions were rejected.
Grade: Sahih

Hadith #5093 - Sunan Abi Dawud - Anas ibn Malik; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Ibn Jurayj ابن جريج; Ishaq bin 'Abdullah bin Abi Talha إسحاق بن عبد الله بن أبي طلحة (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) saw the new moon, he turned away his face from it. Abu Dawud said: On this subject there is no tradition which has perfect chain and is sound.
Grade: Da'if

Hadith #5105 - Sunan Abi Dawud - Abdul 'Aziz bin Jurayj عبد العزيز بن جريج; Da'ud bin 'Abdur Rahman al-'Atar داود بن عبد الرحمن العطار; Ibn Jurayj ابن جريج; Ibrahim bin Abi al-Wzyr Akhw إبراهيم بن أبي الوزير; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) uttering the call to prayer (Adhan) in the ear of al-Hasan ibn Ali when Fatimah gave birth to him.
Grade: Hasan

Hadith #5174 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Abi Sufyan bin 'Abdur Rahman عمرو بن أبي سفيان بن عبد الرحمن; Ibn Jurayj ابن جريج; Kulda bin al-Hanbal; Muhammad bin Bashar Bindar محمد بن بشار بندار; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي (Sunan Abi Dawud)
A man came. Uthman’s version has: Sa’d ibn AbuWaqqas came. He stood at the door. Uthman’s version has: (He stood) facing the door. The Prophet (ﷺ) said to him: Away from it, (stand) this side or that side. Asking permission is meant to escape from the look of an eye.
Grade: Sahih

Hadith #5180 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Ubaid bin 'Umayr bin Qatada عبيد بن عمير بن قتادة; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي (Sunan Abi Dawud)
I was sitting in one of the meeting of the Ansar. Abu Musa came terrified. We asked him; what makes you terrified? He replied: ‘Umar sent for me; so I went to him and asked his permission three times, but he did not permit me (to enter), so I came back. He asked; what has prevented you from coming to me? I replied: I came and asked permission three times, but it was not granted to me (so I returned). The Messenger of Allah (May peace be upon him) has said: When one of you asks permission three
Grade: Sahih

Hadith #5197 - Sunan Abi Dawud - Abu Hurairah; Ibn Jurayj ابن جريج; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Those who are nearest to Allah are they who are first to give a salutation.
Grade: Sahih

Hadith #5237 - Sunan Abi Dawud - Abdullah bin Hbshy; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Ibn Jurayj ابن جريج; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Muhammad al-Jarmi سعيد بن محمد الجرمي; Uthman bin Abi Sulaiman عثمان بن أبي سليمان بن جبير بن مطعم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out, and on seeing a high-domed building, he said: What is it? His companions replied to him: It belongs to so and so, one of the Ansar. He said: he said nothing but kept the matter in mind. When its owner came and gave him a greeting among the people, he turned away from him. When he had done this several times, the man realised that he was the cause of the anger and the rebuff. So he complained about it to his companions, saying: I swear by Allah that I cannot
Grade: Hasan